The relationship among live hog, carcass, and wholesale cut prices - Keeler, G.L.; Langemeier, Michael R.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
This study examined the relationship between live and carcass prices and the seasonality of live, carcass, and wholesale cut prices. Results using Omaha live prices suggested a unidirectional relationship between live and carcass prices, with farm prices leading carcass prices by 3 weeks. In contrast, the results generated using live prices from the St. Joseph terminal market suggested a bidirectional relationship. Live and carcass prices from 1987 to 1992 were found to be highly correlated. The average monthly price spread between the Omaha live price and the USDA carcass price ranged from $14.02 to $23.18 cwt, with an average spread of $17.53 cwt. The spread has changed only marginally from 1987 to 1992. Loin prices were found to follow the seasonal price pattern of live and carcass prices, except that they declined to a greater degree in October and November. Ham prices also followed the seasonal price trend of live and carcass prices, except that they increased to a greater extent during Thanksgiving and Christmas. The increased support of ham prices in the fall tended to offset the seasonal weakness in loin prices. Seasonality of spare rib prices was evident, with the high prices occurring during the outdoor cooking season (May, June, and July). Boston butt prices followed the seasonal pattern of live and carcass prices. (Key Words: Carcass Price, Live Price, Wholesale Price, and Seasonality.)
Keywords: Swine; Live hog prices; carcass prices; wholesale cut prices